2021
DOI: 10.1016/j.jbc.2021.101246
|View full text |Cite
|
Sign up to set email alerts
|

Replication stress inhibits synthesis of histone mRNAs in yeast by removing Spt10p and Spt21p from the histone promoters

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 85 publications
(149 reference statements)
2
11
0
Order By: Relevance
“…2B). Consistent with previous studies ( 36, 37 ), we found that histone mRNAs in YPD have short half-lives, whereas ACT1 mRNA is more stable. Moreover, we showed that both histone and ACT1 mRNAs are significantly more stable in poor compared to rich nutrient conditions.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…2B). Consistent with previous studies ( 36, 37 ), we found that histone mRNAs in YPD have short half-lives, whereas ACT1 mRNA is more stable. Moreover, we showed that both histone and ACT1 mRNAs are significantly more stable in poor compared to rich nutrient conditions.…”
Section: Resultssupporting
confidence: 93%
“…Relative changes in mRNA concentrations were measured by RT-qPCR as described above. Target-specific primers were designed to bind to the HTB1, HTB2 and ACT1 coding sequences, respectively ( 36 ). The half-lives of histone and ACT1 mRNAs were calculated by fitting a single exponential function to the obtained mRNA decay curves.…”
Section: Methodsmentioning
confidence: 99%
“…In S . cerevisiae, histone synthesis is inhibited following a DNA replication block with the treatment of hydroxyurea (HU) via a specific regulatory coupling (Bhagwat et al . 2021), which is likely mediated by the HIR complex ( hi stone regulatory genes ( HIR1 , HIR2 , HIR3 ) and h istone p eriodic c ontrol gene ( HPC2 )).…”
Section: Resultsmentioning
confidence: 99%
“…Tight control of the regulation of core histones throughout the cell cycle ensures the proper function of DNAtemplated processes (Eriksson et al 2012). Proper stoichiometry between nucleosomes and total DNA content is partly controlled through replication-coupled synthesis of histones (Robbins and Borun 1967), evidenced by experimental inhibition of DNA synthesis leading to rapid repression of histone synthesis (Osley 1991;Rattray and Müller 2012;Bhagwat et al 2021) Moreover, misexpression of histones outside of S-phase characteristically leads to cellular toxicity and growth arrest (Kurat et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…We found that CgSub2 interacted with H2A, with surplus-iron leading to a higher CgSub2-CgH2A interaction, despite a reduction in H2A levels (Fig 6C). Of note, decreased histone H2A levels under surplus-iron conditions may partly be due to general stress-responsive transcriptional downregulation of core histone genes in Cg, as the genotoxic stress is known to result in transcriptional downregulation of the histone H3 and H4 genes in Cg [47], and a reduction in histone mRNAs in S. cerevisiae [48]. Further, our co-immunoprecipitation results point towards the environment cue (iron abundance)responsive interaction of CgSub2 with the canonical histone H2A or the histone H2A variant CgHtz1, which may potentially modulate chromatin dynamics.…”
Section: Cgsub2 Is Essential For Surplus-iron-induced Host Adherencementioning
confidence: 99%